SAMPLING TABLES: AN IMPORTANT STATISTICAL TOOL FOR AUDITORS. - Neter, John (The Accounting Review, 1952)
It is the purpose of this article to describe some of the sampling tables, how they may be used, on what assumptions they are based, and their limitations. Interest in the use of statistical sampling techniques by auditors has grown recently. Articles in the journal "The Accounting Review," (1) The Arthur Andersen Chronicle, (2) The Woman C.P.A. and (3) the Journal of the American Statistical Association (4) testify to this development. The use of statistical techniques can furnish an auditor not only with more objective criteria as to the sample size required and the interpretation of the sample, but it would also probably reduce costs. These advantages have been stressed already. When applying statistical techniques to auditing, it is of great importance that these techniques be used correctly. This is particularly true at the initial stage of application, because poor results from the first uses of statistical tools may very likely lead an auditor to abandon them entirely. While there are definite limitations in the use of the sampling tables discussed in this article, it nevertheless appears clear that these tables can be of great help to the auditor. The selection of an appropriate sampling plan becomes simple, indeed, with the tables.